Aortic valve disorders and left ventricular assist devices - Acharya, Deepak; Kazui, Toshinobu; Al Rameni, Dina; Acharya, Tushar; Betterton, Edward; Juneman, Elizabeth; Loyaga-Rendon, Renzo; Lotun, Kapildeo; Shetty, Ranjith; Chatterjee, Arka (Frontiers in Cardiovascular Medicine, 2023)
Aortic valve disorders are important considerations in advanced heart failure patients being evaluated for left ventricular assist devices (LVAD) and those on LVAD support. Aortic insufficiency (AI) can be present prior to LVAD implantation or develop de novo during LVAD support. It is usually a progressive disorder and can lead to impaired LVAD effectiveness and heart failure symptoms. Severe AI is associated with worsening hemodynamics, increased hospitalizations, and decreased survival in LVAD patients. Diagnosis is made with echocardiographic, device assessment, and/or catheterization studies. Standard echocardiographic criteria for AI are insufficient for accurate diagnosis of AI severity. Management of pre-existing AI includes aortic repair or replacement at the time of LVAD implant. Management of de novo AI on LVAD support is challenging with increased risks of repeat surgical intervention, and percutaneous techniques including transcatheter aortic valve replacement are assuming greater importance. In this manuscript, we provide a comprehensive approach to contemporary diagnosis and management of aortic valve disorders in the setting of LVAD therapy.